Head-to-head, randomised, crossover study of oral versus subcutaneous methotrexate in patients with rheumatoid arthritis: drug-exposure limitations of oral methotrexate at doses ≥15 mg may be overcome with subcutaneous administration. Issue 8 (12th April 2014) - Schiff, Michael H; Jaffe, Jonathan S; Freundlich, Bruce
Abstract : Objective: To compare the relative bioavailability, safety and tolerability of oral methotrexate (MTX) and subcutaneous (SC) MTX administered via an auto-injector (MTXAI) in patients with rheumatoid arthritis (RA). Methods: In this randomised, multicenter, open-label, three-way crossover study, patients ≥18 years with adult RA undergoing treatment with MTX for ≥3 months were assigned to receive MTX 10, 15, 20 and 25 mg weekly in a random sequence of three treatments: oral, SC into the abdomen and SC into the thigh. For 24 h after administration of each treatment, blood samples were collected for pharmacokinetic analysis and injection sites were assessed. Results: Forty-seven patients completed the study. Systemic exposure of oral MTX plateaued at doses ≥15 mg/week. In contrast, SC MTX demonstrated a linear increase in systemic exposure that was greater than oral MTX at each dose. No unexpected AEs were noted for either formulation. Conclusions: Unlike oral MTX, the systemic exposure of SC MTX did not plateau over the doses studied, particularly at doses ≥15 mg/week. In this study, higher systemic MTX exposure was not associated with increases in AEs. Patients with an inadequate clinical response to oral MTX may benefit from higher drug exposure by switching to SC MTX. Trial registration number: NCT01618968.